Partnered women's contribution to household labor income: Persistent inequalities among couples and their determinants - Martina Dieckhoff; Vanessa Gash; Antje Mertens; Laura Romeu Gordo (Social Science Research, 2019)
This paper explores earnings inequalities within dual-earner couples in East and West Germany drawing on household-level panel data from 1992 to 2016. It has three aims: (1) to analyze how the partner pay gap (the pay gap between partners within one household) has developed over time, given institutional change, and whether the extent of inequality and temporal development vary between East and West Germany; (2) to explore variation in the partner pay gap by male partners' absolute earnings; and (3) to investigate the micro-level determinants of earnings inequalities within couples and determine whether their relevance varies between East and West Germany as well as by male partners' absolute earnings. We find women earn substantially less than their partners, and our regression results find no indication of a declining partner pay gap. Besides substantial variation between East and West Germany, our results also reveal important group-specific variation in the extent of the partner pay gap as well as in its determinants.
Keywords: 300; partner pay gap; gender inequality; employment; institutional change; time trends